Use of Normal-colour Aerial Photographs in Collection of Data for Reforestation Assessment - Bansal, A. K.; Murtha, Peter A. (Indian Forester, 1989)
Satellite remote sensing is a major technological advance that has revolutionized information gathering about the Earths natural resources. Improved spatial and spectral characteristics of Landsat thematic mapper data seem to have the potential for extending the usefulness of remotely sensed data in detailed assesment of forest resources. Collection of adequate ground truth is a necessary prerequisite for evaluating the informotion content of TM data with regald to stocking status over ruegetating lands This paper discusses the use of medium scale normal colour aerial photographs for obtaining prtcise estimates of forest stocking over clearcut forest lands.